Local community’s intention to participate in sustainable mangrove forest program in Malaysia - Wahid Marican, Nurshahirah (2018)
Mangrove forest play an important role in balancing the ecosystem since Mangrove trees provides a breeding ground for flora and fauna. In Malaysia, Mangrove forest can be found mainly in Sabah and Sarawak covering about 83% of the total Mangrove forest in Malaysia. Peninsular Malaysia only has 17% of Mangrove forest which are located mainly in the west coast, from Kedah, Perak, and Selangor up to south of Johor. Government bodies and NGO have been working to replant and increase public awareness to protect the Mangrove forest in this past few years. Despite all of this, Malaysia’s Mangroves have declined over 45% in the past five decades from an estimated 1.1 million hectares to the current estimate of 564,970 hectares. Past studies have showed that the public participation in mangrove forest programs are still low and stagnant due to lack of awareness. There are also socio-economic factors with several contributing elements such as awareness, perception, attitude, and perceived behavioural control that affects the local community’s intention to participate in the Mangrove sustainable programs. Thus, this study would like to understand the local community’s intention to participate in the sustainable Mangrove forest programs in Malaysia. The Theory of Planned Behaviour and Norm Activation Theory are used in this study for the development of the main framework. The study specifically have been conducted in the states that has a higher Mangrove forest percentage; Sabah, Selangor, Perak, Pahang, and Johor. A structure questionnaire were used to collect a total of 871 respondents that has been selected using stratified random sampling. Then, the data were analysed using descriptive analysis, chisquare analysis, factor analysis and multiple regression analysis. Chi-square analysis was applied to determine the relationship between the sociodemographic factors and the intention to participate in the sustainable Mangrove forest programs. Next, factor analysis was used to explore the determinant factors influencing the local community’s intention to participate in the programs. Multiple regression analysis was applied to determine the relationship between socio-demographic factors, extracted factors and local community’s intention to participate in sustainable Mangrove forest programs. This study has discovered that respondents have good awareness towards the importance of Mangrove forest. The findings on chi-square analysis showed that age, education level, income level, household size and lifestyle have significant association with respondent’s intention to participate in the sustainable Mangrove forest programs. Factor analysis has identified eight factors namely environmental benefits, public opinions, ecosystem benefits, public influence, convenient, public encouragement, anti-anthropocentrism, and practicality. The most influencing factors identified using multiple regression are environmental benefits, public opinions, public influence, convenient, and public encouragement with the addition of perception and socio-demographics characteristic such as age and education level. This study has also discovered a new factor and employed a new framework which is a combination between TPB and NAT. The findings from this study can assist the government and NGO to develop programs based on the local community needs.